Analisis Pendapat Siswa Tentang Pembelajaran Berbasis Media Televisi Selama Pandemi Covid-19 - Rages Wari; Luthfi Hamdani Maula (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Education is the main means of improving the quality of human resources, without education it will be difficult to obtain maximum results from the quality of human resources. As a result of the covid-19 pandemic, various policies were implemented to break the chain of spreading the covid-19 virus in Indonesia. The Covid-19 pandemic has a major impact on various sectors, one of which is education. The world of education also feels the impact. Educators must ensure teaching and learning activities continue, even though students are at home. The solution, educators are required to design learning media as an innovation by utilizing online media. This is in accordance with the Minister of Education and Culture of the Republic of Indonesia regarding Circular Number 4 of 2020 concerning Implementation of Education Policies in an Emergency for the Spread of Corona Virus Disease (Covid-19). The learning system is implemented through television media. Educators can learn together at the same time using groups on social media such as WhatsApp (WA), telegram, Instagram, zoom applications or other media as learning media. Thus, educators can ensure students follow the learning at the same time, even though in different places. Educators can also give measurable assignments in accordance with the objectives of the material presented to students. However, cases that often occur when the application of television media-based learning systems include, not all students have TVRI television channels, the purpose of this study is to describe the opinions of third grade students about television media-based learning during the pandemic. This research uses descriptive qualitative research methods.